PENGEMBANGAN MODEL KONSELING KARIR BERBASIS MEDIA FILM ANIMASI UNTUK MENINGKATKAN KOMPETENSI KARIR PESERTA DIDIK DI SEKOLAH DASAR - Siwabessy, Louise (Parameter, 2015)
Abstract: The main aims during the three-year study is to produce counseling model based on animation film MAKSaD media that effective for improving the career competence of students in elementary school (SD). The specific objective of the study was to get: (1) model of animated film career ready MAKSaD media tested is limited; (2) model of media animated film career MAKSaD to improve the competence of elementary school students career test results are ready to be tested is limited diperluar; and (3) scientific articles published in national or international journals. Research methods of research and development (Research and Development). The research sample for validation MAKSaD media animated film career is an expert guidance and counseling, information and communication technology experts and practitioners (elementary class teacher). Collecting data using medium quality instruments. Data were analyzed using descriptive statistics Mean. Results of this research are the validation resultan by BK experts, ICT specialists and primary class teachers to media careers animated films in general are in very good category with a mean score of 3.6 (the expert ICT) and 3.4 (practitioners / teachers grade SD) on a scale 1-4. Abstrak: Tujuan utama penelitian selama tiga tahun adalah menghasilkan model konseling berbasis media film animasi MAKSaD yang efektif untuk meningkatkan kompetensi karier peserta didik di Sekolah Dasar (SD). Tujuan khusus penelitian tahun kedua adalah mendapatkan: (1) model media film animasi karier MAKSaD yang siap diuji coba terbatas; (2) model media film animasi karier MAKSaD untuk meningkatkan kompetensi karier peserta didik SD hasil uji coba terbatas yang siap diuji coba diperluar; dan (3) artikel ilmiah yang dimuat di jurnal nasional atau internasional. Penelitian menggunakan metode penelitian dan pengembangan (research and Development). Sampel penelitian untuk validasi media film animasi karir MAKSaD adalah pakar bimbingan dan konseling, pakar teknologi informasi dan komunikasi, dan praktisi (guru kelas SD). Pengumpulan data menggunakan instrumen kualitas media. Teknik analisis data menggunakan statistik deskriptif berupa rerata. Hasil penelitian yaitu hasil validasi pakar BK, pakar TIK, dan guru kelas SD terhadap media film animasi karir secara umum berada pada kategori sangat baik dengan rerata skor 3,6 (pakar TIK) dan 3,4 (praktisi/ guru kelas SD) pada skala 1-4.